Burkholderia cenocepacia Differential Gene Expression during Host–Pathogen Interactions and Adaptation to the Host Environment - O'Grady, Eoin P.; Sokol, Pamela A. (Frontiers in Cellular and Infection Microbiology, 2011)
Members of the Burkholderia cepacia complex (Bcc) are important in medical, biotechnological, and agricultural disciplines. These bacteria naturally occur in soil and water environments and have adapted to survive in association with plants and animals including humans. All Bcc species are opportunistic pathogens including Burkholderia cenocepacia that causes infections in cystic fibrosis and chronic granulomatous disease patients. The adaptation of B. cenocepacia to the host environment was assessed in a rat chronic respiratory infection model and compared to that of high cell-density in vitro grown cultures using transcriptomics. The distribution of genes differentially expressed on chromosomes 1, 2, and 3 was relatively proportional to the size of each genomic element, whereas the proportion of plasmid-encoded genes differentially expressed was much higher relative to its size and most genes were induced in vivo. The majority of genes encoding known virulence factors, components of types II and III secretion systems and chromosome 2-encoded type IV secretion system were similarly expressed between in vitro and in vivo environments. Lower expression in vivo was detected for genes encoding N-acyl-homoserine lactone synthase CepI, orphan LuxR homolog CepR2, zinc metalloproteases ZmpA and ZmpB, LysR-type transcriptional regulator ShvR, nematocidal protein AidA, and genes associated with flagellar motility, Flp type pilus formation, and type VI secretion. Plasmid-encoded type IV secretion genes were markedly induced in vivo. Additional genes induced in vivo included genes predicted to be involved in osmotic stress adaptation or intracellular survival, metal ion, and nutrient transport, as well as those encoding outer membrane proteins. Genes identified in this study are potentially important for virulence during host–pathogen interactions and may be associated with survival and adaptation to the host environment during chronic lung infections.